Development of the Unit Evaporator Cleaner Prototype in Air Conditioning - Muhamad Khalid Hossin; Yunus, Faizal Amin Nur (Research and Innovation in Technical and Vocational Education and Training, 2025)
Air quality plays an important role in health and can also improve the performance of workers in the office. Among the reasons for the decrease in air quality in a room is because the air conditioning is not maintained at the right time. The cleanliness of the evaporator on the indoor unit can ensure that the air in the room is in good condition. The air conditioning unit evaporator cleaner prototype, which recycles the condensation water from the air conditioner, is an inventive way to create a prototype that can guarantee the evaporator runs at peak efficiency. The developed prototype is equipped with an IoT system operated through the Blynk application, making it easy for users to control and set the system to operate at the desired time. The main objective of this study is to design, develop and test the functionality of a prototype evaporator cleaner unit in air conditioning. The ADDIE model is used as a developmental model that serves as a guiding framework for this research. In addition, three experts from among air conditioning lecturers and also external experts were involved in testing and evaluating the functionality of the prototype of the evaporator cleaner unit in the air conditioner that was developed. The evaluation results show that the percentage of expert agreement is 100% for two items and three items show deficiencies with 66.7%, 33.33% and 66.67% respectively for the question items in part B. While for the question items in part C, two items show a percentage of 66.67 % and four items show 100% agreement. For question items in part D, all items show a percentage of 100%. For question items that show a percentage reduction or disagree, there are comments and improvement suggestions provided by each expert to serve as a reference and guide for further improvement and improve the overall effectiveness of the product in future studies.